The CA3 region of the hippocampus: how is it? what is it for? how does it do it? - Enrico Cherubini; Richard Miles (Frontiers Media SA, 2015)
The aim of this special topic is to bring together experts on the cellular and molecular mechanisms regulating the wiring properties of the CA3 hippocampal microcircuit in both physiological and pathological conditions, synaptic plasticity, behavior and cognition.We will particularly emphasize the dual glutamatergic and GABAergic phenotype of MF-CA3 synapses at early developmental stages and the steps that regulate the integration of newly generated neurons into the adult dentate gyrus-CA3 circuit.
English
Keywords: episodic memory; mossy fibers; Associative network; spatial representation; CA3 subfield; Hippocampus; Theta Rhythm